Improved disjunctive models for the transmission expansion planning - Escobar, Laura M.; Escobar, Antonio H.; Romero, Ruben A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
This paper presents two improved disjunctive models for the transmission expansion planning problem, with the inclusion of additional critic cycles has been developed by the authors in recent works, in order to improve some of the traditional long-term transmission network expansion planning problem models. The reason behind it is the absence of Kirchhoff second law which completes the representation of the transmission system, but increase the complexity, making some big-sized problems impossible to solve depending of their topology. This improvement will allow the model to be solve the majority of the test systems with less computational effort and in less time. For specific cases the improved models help find better solution, which can be used as an starting point to find the optimal solution. The new models are implemented in AMPL, using the solver CPLEX. This paper uses the Colombian test system to illustrate the effectiveness of the proposed framework.
Keywords: Improved disjunctive transportation model; Mathematical modeling; Mixed-integer linear programming; Transmission expansion planning